Diferencias regionales y Síndrome Pulmonar por Hantavirus (enfermedad emergente y tropical en Argentina) - Sosa-Estani, Sergio (2001)
Factors related to the characteristics of Hantavirus pulmonary syndrome in Argentina are described. Factors from different scientific fields converge to form the syndrome’s analytical framework. Some of these factors are the history of spatial occupation, work and production structures, human migration patterns, ethnic composition, reservoir dynamics and its relationship to the different circulating viruses, and human behavior. Furthermore, the multiple factors are expressed in three ecological frameworks, associated with three different geographical regions of Argentina: 1) Northwest; 2) Central (“wet Pampa”); and 3) South Andean. In order to understand the actual causality of health or disease as an interaction of many factors, research on the primary biological, social, and environmental determinants of diseases should attend to the complexity of variable relationships in each region. The multiple-factor convergence approach allows for the design of appropriate strategies to improve the population’s health status. Therefore, strategies should be developed and transferred by multidisciplinary teams, while their sustainability should be assured by community participation beginning with the earliest steps of research onward.